Determination Of Notary Service Fees For The Preparation Of Authentic Deeds In Payakumbuh City - Rani Permata Sari; Ali Arben (Ilmu Hukum Prima (IHP), 2026)
The emergence of improper competition among notaries is partly due to the imposition of service charges or honorariums that are lower than the provisions outlined in the Law and the Ethical Guidelines. This is very contrary to what is regulated by the UUJN and the Notary Code of Ethics, because notaries are prohibited from making efforts to determine service rates below the standard to get as many clients as possible, but in practice there are notaries who do this. For this reason, in cases like this, there needs to be supervision by the Notary Supervisory Board regarding the implementation of Notary honorariums. "From several percent of the sociological and economic value needs to be determined" This is very difficult because the Notary determines the exact sociological value of the deeds being made. In reality, UUJN Article 36 paragraph 2 is less than satisfactory, it can be said that the amount of honorarium made by public officials is based on the exact economic value and the exact sociological value of all deeds made. a public official whose function is to prepare authentic deeds. The code of ethics aims to ensure that every action taken by a notary is based on the principles of professionalism, objectivity, and the interests of the community and the state.